Motherhood Versus Metropolis: Maternity Practices in Native Cultures of the Chronicles of Peru - Diana Eguía Armenteros (European Scientific Journal, ESJ, 2020)
Motherhood and colonization, why should we put these two notions together, and what do we know about the changes in childbearing patterns during the colonization of the America’s as a signal of a broader cultural change? Even when all human life on this planet is born from a woman, we know more about the air we breathe, and the seas we travel, than about the nature and meaning of motherhood as Adrienne Rich famously said (1976: 11). The production of life remains a marginal issue in the study of modernity and its consequences. The colonization of America marked a significant shift in how Western minds understood themselves and was pivotal in the overall concept of motherhood and by combining both these cultural phenomena we can illuminate many aspects of society, then and now.